The Effect of Online Learning, Educational Technology on Learning Interest during the Covid-19 Pandemic (Edukasi, 2022)
The pandemic that hit the world, including Indonesia, had an impact on all sectors, not involving the education sector. This has an impact with the implementation of distance learning with a bold learning system and Educational Technology. Because the remote education system is still able to deliver lecture material well to students. This study aims to find out whether bold learning, Educational Technology carried out by lecturers at STIE can increase student interest in learning about effective subjects. The population in this study were Accounting students at the SEMARANG College of Economics. 126 Students received 40 samples using purposive sampling technique. The independent variables of this study were daring learning, educational technology and dependence on interest in learning. The method used in this study was multiple regression analysis. The results of this study indicate that the significance value for the Online Learning variable is 0.145 which means more than 0.05 and t count is 0.231 t table which is 1.217 so Ha is rejected. Learning to be brave has no significant effect on interest in learning. The significance value for the educational technology variable is 0.663, which means less than 0.05 and t count is 0.000 t table which is 3.824 so Ha is accepted. Educational technology has a significant effect on interest in learning. The determinant coefficient value obtained is 0.336, this means that 33.6% of learning interest is influenced by online learning, educational technology.